Village development performance catalyst based on village fund priorities in plant and animal food security in the Tomini Bay Area - Hippy, Mohammad Zubair; Aisyah R, ST.; Boekoesoe, Yuriko; Saleh, Yanti; Moonti, Agustinus; Mustafa, Ramlan; Machieu, Siti Rahmatia (AGROMIX, 2025)
Introduction: Food security programs have become a strategic issue that consistently attracts the attention of various levels of government, including village governments, as regulated in the Minister of Village, Development of Disadvantaged Regions, and Transmigration of the Republic of Indonesia. Thus, this program will create sustainable food security, which is also a measure of the success of rural development. Methods: This research is a quantitative study. The data source in this research is primary data obtained through the distribution of questionnaires to the district government, villages, and farmers, in accordance with the sample calculation requirements of 213 farmers, as well as through interviews and field observations. The data analysis techniques used are descriptive analysis and Structural Equation Modeling (SEM) PLS. Results: (1) village development performance, resource management, collaboration and creativity of the farmer-breeder community is on fairly good criteria (2) resource management has a positive and significant effect on collaboration, resource management has a positive and significant effect on the creativity of farmer-breeders, resource management has a positive but insignificant effect on village development performance, collaboration has a positive and significant effect on village development performance, the creativity of farmer-breeders has a positive and significant effect on village development performance, resource management through collaboration has a positive and significant effect on village development performance, the creativity of farmer-breeders has a positive and significant effect on village development performance. Conclusion: collaboration and creativity of farmer-breeders are good mediating variables as they can enhance the influence of resource management on village development performance based on the priorities of village funds in plant and animal food security.